Stress strained state change in the «deformed building – pile foundation – base» system resulting from supplying the slab under the grilles - Vynnykov, Yuriy; Kharchenko, Maksym; Manzhalii, Sergii (Academic journal Industrial Machine Building Civil Engineering, 2020)
Presented features of a new analytical model of the "deformed building - driven prismatic piles as a part of a continuous grille - soil base with a weak underlying layer" system before and after supplying the monolithic reinforced concrete slab under the existing foundation grilles. Also, this system’s stress strained state (SSS) simulation results by the finite element method (FEM) for evaluation of the combined action features of the system’s components were presented. It has been published the new empirical data on the SSS change in the "deformed building - driven prismatic piles as a part of a continuous grille - soil base with a weak underlying layer" system resulting from supplying the monolithic reinforced concrete slab under the existing foundation grilles.